Occupational Factors with Toddler Nutrition Status - Rizka Esty Safriana; Endah Mulyani; Aidha Rachmawati (JURNAL KEBIDANAN, 2019)
Toddler is one of the groups prone to malnutrition because it can cause death. Parents, especially mothers, play a role in fulfilling the nutritional status of toddlers. The purpose of this study was to determine the relationship of maternal employment with the nutritional status of toodler in Tebul Timur Village, Pegantenan District, Pamekasan Regency. The design of this research was observational analytic method with cross sectional approach. Population 251 mothers and toodlers. The sampling technique uses simple random sampling. The sample used was 154 mothers and toodlers. The majority of maternal employment are 93 people (60.4%) and almost all toddlers have good nutritional status as many as 130 children (84.4%). Based on the Lambda test results, the p value (0.018) α (0.05) means that statistically there is a relationship between maternal employment and the nutritional status of toodler in Tebul-Timur Village, Pegantenan District Pamekasan.